Sustainability: Post-pandemic corporate accountability - Jeremy Cripps (University American College Skopje, 2021)
Corporate accountability refers to company performance in "non-financial areas" especially sustainability." Post Pandemic corporate accountability requires actions, decisions, policies which operate "outside the box." The revolutionary Covid19 mRNA vaccines are a clear and timely call to corporate boards to challenge "traditional" approaches to sustainability in the way Moderna and other vaccine manufacturers arrived at their new vaccine sustainability. Major corporations are already recognizing the potential for reduced commuter activity and trying to take a life-cycle costing approach to changes that may be made as their present contracts for commercial space and office "overhead" are coming up for renewal. Software technology for expanding work at home and integrating with cloud-based scalable video conferencing and remote access systems to engage your customers in your business processes is developing at speed. This paper is about post pandemic sustainability thinking. We discuss how the capacity to recover from difficulties may be improved in several areas. Indoors, with examples, we consider the impact of inner space as the next corporate frontier - the impact of contagious disease prevention and the culture of office plant propagation. We find the potential for florafelt pocket systems, vertical hydroponic gardens, biowalls, living rooves, and garden treasuries of plants and products from revolutionary science already underway. Socio-ecological system elasticity is considered and the examination of insights on creating sustainability in a warming world.
Keywords: 330; Corporate accountability; social responsibility; sustainability; inner space revolution; socio-ecological thinker